Warfarin Clinic Integration and Development of Health Service Systematic Network by Pharmaceutical Care, Pattani Province - ตันติวิชญวานิช เจนจิรา (Journal of Health Science of Thailand, 2021)
Warfarin is anticoagulants of high risk oral type. Adverse drug event could be found in bleeding state. The use of this medicine is complex and it has to be adapted to fit with each patient. Therefore, it needs good management for patients to receive proper, effective and safe medicine. The objective of this study was develop pharmaceutical care system with a multidisciplinary team, and develop warfarin clinic network in Pattani Province. It was conducted as a descriptive study. The study samples were all 704 patients utilizing warfarin at Pattani hospital during the period from October 2012 to September 2018. Initial comparison between pre-study and post-study of pharmaceutical care on 2012 revealed that the warfarin clinical service pattern was similar to the service of a general clinic: the patients met doctors, then pharmacists gave pharmaceutical care. Such system was found to be unsafe to the patients. As a result, this research was initiated, covering the period from 2013 to 2018, began with the establishment of warfarin clinic and a new healthcare service integration. The process had been continuously improving by applying design thinking for modern inventions that supports pharmaceutical care to be more effective. Then, in 2016-2018, the health service network and pharmaceutical care was expanded to cover the whole province. Throughout the research phase, data were collected using pharmaceutical care evaluation form, and were analyzed data using descriptive statistics. It was found that after development of health service system, the number of problems relating to drug utilization reduced from 34.82 to 6.64 percent. The percentage of INR (International Normalized Ratio) was in kept in the target range with an increasing tendency from 36.64 to 63.02 percent. Adverse drug events reduced from 8.95 to 0.95 percent; and the prescription errors had decreased from 103.03 to 9.62 per thousands prescriptions. In conclusion, the warfarin clinic development which collaborated pharmaceutical care with the multidisciplinary team had been effective in keeping patients safe, and reducing unwanted symptoms from drug use. Thus, the development of warfarin clinic network with the participation of community hospitals and sub-district health promotion hospitals helped the patients receiving intimate care which was effective, convenient, and safe.